Speech Strategy Used by Moderator for Revealing Valuable Information in Discussion - Laila, Malikatul (Universitas Muhammadiyah Surakarta, 2015)
To reveal information within a discussion, moderator usually implements strategies to leverage the addressee to arouse more responses. This paper aims to investigate moderators’ speech strategies in tvOne discussion, Indonesia Lawyers Club (ILC). The data were utterances during the session of discussion collected by using purposive sampling and the results areten different topics performed onevery Tuesday night from 8 to 11 p.m. in 2012. The technique for analyzing data iscomprehensive analysis referring to pragmatic context both for the strategies of speech act by Searle (1979) and maxims of Cooperative Principles by Grice (1989). The findings show that the most powerful moderators’ speech strategy used to reveal information is directly literal speech act strategy, with the variations of: (1) signaling the adressee with/or without speaking verbally;this signal of non-verbal language is used to show and reveal intimacy; (2) repeating the addressee’s words to show more response to the addressee; (3) using suggestingformula to give respect, especially to addressee with higher status; (4) making counter to ones’ opinions to prove the realinformation;and (5) presenting polite criticism to remark the answer, in which the latter presented less indirectly.